2013
DOI: 10.1074/jbc.m112.412403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Site in the Tail of Dynein Heavy Chain Important for Dynein Function in Vivo

Abstract: Background:The dynein heavy chain tail is required for subunit interactions but not for in vitro motility. Results: A dynein tail mutation affects dynein function in vivo without affecting subunit interactions. Conclusion: A site upstream of the subunit interaction sites of the dynein tail is important in vivo. Significance: This study discovers a novel site of the dynein tail critical for motor function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 79 publications
2
24
0
Order By: Relevance
“…To do that, we examined the effect of a previously identified dynein loss-offunction mutation, nudA F208V . The nudA F208V mutation in the dynein tail impairs dynein-mediated nuclear distribution and early endosome transport but does not affect dynein-dynactin interaction or dynein-early-endosome interaction (Qiu et al, 2013), consistent with the importance of the tail in dynein motor activity (Ori-McKenney et al, 2010;Rao et al, 2013;Hoang et al, 2017). Upon overexpression of ΔC-HookA, plus-end comets formed by GFP-dynein with the nudA F208V mutation were still detected ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…To do that, we examined the effect of a previously identified dynein loss-offunction mutation, nudA F208V . The nudA F208V mutation in the dynein tail impairs dynein-mediated nuclear distribution and early endosome transport but does not affect dynein-dynactin interaction or dynein-early-endosome interaction (Qiu et al, 2013), consistent with the importance of the tail in dynein motor activity (Ori-McKenney et al, 2010;Rao et al, 2013;Hoang et al, 2017). Upon overexpression of ΔC-HookA, plus-end comets formed by GFP-dynein with the nudA F208V mutation were still detected ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…To do that, we examined the effect of a previously identified dynein loss-of-function mutation, nudA F208V . The nudA F208V mutation in the dynein tail impairs dynein-mediated nuclear distribution and early endosome transport but does not affect dynein-dynactin interaction or dynein-early endosome interaction (Qiu et al, 2013), consistent with the importance of the tail in dynein motor activity (Ori-McKenney et al, 2010;Rao et al, 2013;Hoang et al, 2017). Upon overexpression of ∆C-HookA, plus-end comets formed by GFP-dynein with the nudA F208V mutation were still detected ( Figure 1I), confirming that functional dynein is needed for this relocation.…”
Section: Dynein and Dynactin Are Relocated From The Mt Plus Ends To Tsupporting
confidence: 63%
“…Quantitation of the protein band intensity was done using the IPLab software as described previously (Qiu et al, 2013). The antibody against GFP (polyclonal) was from Takara Bio Inc.…”
Section: Biochemical Pull-down Assays and Western Analysismentioning
confidence: 99%
“…Because the study was performed in the absence of processivity activators it is, however, unclear how the findings relate to our observations of the effect of the Loa mutation on dynein-dynactin-BICD2N complexes. It has also be demonstrated that a mutation in the tail of DYNC1H1 in the filamentous fungus Aspergillus nidulans (in a residue equivalent to position 186 of the human protein) reduces the frequency and velocity of minus end-directed cargo transport in vivo without affecting the composition of the dynein complex or its association with dynactin (62). Our study reveals that the ability of the tail to regulate the behavior of the motor domain is not just restricted to the regions containing the Loa and Aspergillus mutations.…”
Section: Mechanistic Effects Of Disease-associated Dync1h1 Mutationsmentioning
confidence: 99%